Research on the Quantitative Impact of Power Angle Oscillations on Transient Voltage Stability in AC/DC Receiving-End Power Grids - Long Peng; Shiyun Xu; Zeyuan An; Yi Wang; Bo Wang (Energies)
In practical engineering, it has been observed that increasing local generators’ capacity in receiving-end power grids can lead the system to transition from voltage instability to power angle instability after a fault. This contradicts the typical engineering experience, where increasing the generators’ capacity at the receiving end is expected to enhance voltage stability, making it challenging to define an appropriate pre-control range for generators. This paper aims to quantify the impact of local generators on the stability of AC/DC receiving-end power grids. First, the paper describes the instability phenomena observed under different generators’ capacity conditions in actual AC/DC receiving-end power grids. Next, by using a simplified single-machine-load-infinite-bus model, the paper explores how the system’s instability characteristics evolve from being dominated by load instability to being driven by generator instability as the ratio of local generators to load varies. This study conducts an in-depth analysis of the coupling mechanism between power angle stability and voltage stability. For the first time, it quantitatively characterizes the stable operating region of the system using power angle and induction motor slip as dual constraint conditions, providing a new theoretical framework for power system stability analysis. Additionally, addressing the lack of quantitative research on the upper limit of generator operation in current systems, this study constructs post-fault power recovery curves for loads and DC power sources. Based on the equal-area criterion, it proposes a quantitative index for the upper limit of local generator operation, filling a research gap in this field and providing a crucial theoretical basis and reference for practical power system operation and dispatch.